Capitu e o capítulo: infiltrations, survivals and interstices: infiltrações, sobrevivências e interstícios (TEL Tempo, Espaço e Linguagem, 2022)
Abstract: Digressions on the cinematographic translation of Dom Casmurro by filmmaker Júlio Bressane. Under the guidance of the history of images by Aby Warburg, the creative and experimental reading of the famous novel by Machado de Assis brings together potential reflections on memory, the past and the survival of ancient forces from other times and worlds. Keywords: Dom Casmurro, Machado de Assis, Júlio Bressane, Capitu e o capítulo, transcriation